2012
DOI: 10.1002/app.38211
|View full text |Cite
|
Sign up to set email alerts
|

The electrospun polyamide 6 nanofiber membranes used as high efficiency filter materials: Filtration potential, thermal treatment, and their continuous production

Abstract: In this article, polyamide (PA) 6 was dissolved in 98 wt % formic acids with a concentration of 13 wt %, and then the electrospun PA 6 nanofiber membranes were prepared. The filtration potential of the nanofiber membranes were firstly analyzed based on the scanning electron microscope images and pore size measurements, and then the effects of thermal treatment on the dimensional stability were studied. Subsequently, the continuous production process based on the above experiments and the deposition areas of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…Compared to the primary fibers, the SVA-treated fibers with the same parameters of 15 kV, 25 cm, and 1 mL h −1 and the same volume of 3 mL show significantly increased PM2.5 removal efficiencies by about 6.37% with increasing the specific surface area. Besides the volume of the spinning precursor solution and the surface structure of the fiber, another important parameter for the air filtration mat is the filter's dimension, which also affects the PM2.5 removal efficiency [76][77][78]. In this study, we used an air filtration mat with two other parameters (Sample 2 and Sample 3) to test the PM2.5 removal efficiency.…”
Section: Pm25 Removal Performances Of Air Filtration Matsmentioning
confidence: 99%
“…Compared to the primary fibers, the SVA-treated fibers with the same parameters of 15 kV, 25 cm, and 1 mL h −1 and the same volume of 3 mL show significantly increased PM2.5 removal efficiencies by about 6.37% with increasing the specific surface area. Besides the volume of the spinning precursor solution and the surface structure of the fiber, another important parameter for the air filtration mat is the filter's dimension, which also affects the PM2.5 removal efficiency [76][77][78]. In this study, we used an air filtration mat with two other parameters (Sample 2 and Sample 3) to test the PM2.5 removal efficiency.…”
Section: Pm25 Removal Performances Of Air Filtration Matsmentioning
confidence: 99%
“…After 1,500 cycles of repeated compression and torsion, the PA-6 nanofiber layer was still firmly attached to the support, while mechanical damage is visible in some areas [32]. Recently, Guibo and co-workers [33] reported the preparation of high-efficiency PA-6 filter membrane and investigated the mechanical properties of the resultant membranes. The stress-strain measurements revealed that the heat treatment had significantly affected the mechanical properties of electrospun membranes.…”
Section: Polyamide (Pa)mentioning
confidence: 98%
“…PA6 is a material widely used in a variety of applications including the automotive and textile industries, medicine and engineering. Its high mechanical strength in a wet and dry state [19], hydrophilicity and chemical resistance [20] make it an appropriate material for desalination, textiles [21], various filtration [22] and medical applications [23] water purification and gas separation. Additionally, PA6 can be modified with antibacterial/antifungal agents [24] and is often used in electrospun form for filtration, medical applications and textiles.…”
Section: Introductionmentioning
confidence: 99%
“…PA6 has been well studied using nozzle electrospinning [11], [14], [22] and [25] whereas, to the best of our knowledge, only limited research has been done using the Nanospider needleless methodology [21] and [24]. Researchers focused on the antibacterial additives to PA6 and morphological properties of the fiber's surface depending on the distance between electrodes [21] and [24].…”
Section: Introductionmentioning
confidence: 99%